The Omo-Turkana Basin : cooperation for sustainable water management - Lautze, Jonathan; McCartney, Matthew P.; Gibson, Julie (London : Routledge, 2022)
This book provides a comprehensive examination of water resource management in the Omo-Turkana Basin, linking together biophysical, socioeconomic, policy, institutional and governance issues in a solutions-oriented manner. The Omo-Turkana Basin is one of the most important lake basins in Africa, and despite the likely transboundary impacts associated with the management of dams, it is the largest lake basin in Africa without a cooperative water agreement. This volume provides a foundation for integrated decision-making in the management of development in the Lake Turkana Basin. Chapters cover water-related conditions, hydropower, agriculture, ecosystems, resilience and transboundary governance. The final chapter proposes ways forward in light of the potential benefits that can be achieved through cooperation, and practical realities that cooperation is slow and may take time to achieve. This book will be of great interest to students and scholars of water and natural resource management, environmental policy, sustainable development and African studies. It will also be relevant to water management professionals.
1. IntroductionJonathan Lautze, Matthew McCartney and Julie Gibson2. Climate, Water and Land Resources: Diversity, Uses and ChangesStefaan Dondeyne, Gladys Kangi, Ine Rosier, Henok Kassa and Jos Van Orshoven3. Hydropower Development: Economic and Environmental Benefits and RisksMarta Zaniolo, Matteo Giuliani, Amare Bantider and Andrea Castelletti4. Agriculture, Food and Nutrition SecurityBancy Mati and Douglas J. Merrey5. Ecosystem Services in Changing Social-Ecological SystemsFritz Kleinschroth, Wolde Mekuria, Christian Schwatke and Matthew McCartney6. Resilience Dynamics in a Rapidly Changing Socio-Ecological System: Shifting Inequalities in Ethiopiaś Lower Omo ValleyJennifer Hodbod, Edward G.J. Stevenson and Mercy Fekadu Mulugeta7. Pathways to Enhanced CooperationJulie Gibson and Zeray Yihdego8. First Steps Toward Cooperative Basin ManagementJonathan Lautze, Matthew McCartney and Julie Gibson
Includes index.
Keywords: NATURE / Ecology; NATURE / Environmental Conservation & Protection; NATURE / Lakes & Ponds; Water-supply -- Turkana, Lake (Kenya and Ethiopia) -- Management; Water-supply -- Omo River Valley (Ethiopia and Kenya) -- Management; Water-supply -- Turkana, Lake (Kenya and Ethiopia) -- International cooperation; Water-supply -- Omo River Valley (Ethiopia and Kenya) -- International cooperation; Water resources development -- Turkana, Lake (Kenya and Ethiopia); Water resources development -- Omo River Valley (Ethiopia and Kenya); Sustainable development -- Turkana, Lake (Kenya and Ethiopia); Sustainable development -- Omo River Valley (Ethiopia and Kenya)